(3GdJShjb aj Xd YOe hLhO fXGe eYdheGJ (B:s (3efgL EbJUGOj EOGQj eJcGed ddJYGed eY GdeLghd aj GdCShGb GdeMdjI hGdOhdjI ddSdY hGdNOeGJ hGdCacGQ (B/s - (3GdNVjQj, eMSf GMeOs ((3GdbGgQI(B: s (3GjJQGc ddfTQ h GdJhRjY(B, s, 1996)
(3JLO aj gPG GdcJGH GdefgL GdeJcGed ddJYGed eY GdeLghd ,OhQ GdJShjb aj GdfTGW GdEbJUGOj ,OhQ GdJShjb aj GdShb GdeMdj hGdShb GdYGdej , GdJYHFI hGdJZdja ddefJLGJ GdehLgI ddJUOjQ ,JQhjL GdNOeGJ hGdefJLGJ ,JWhjQ eRjL GdSdY hGdNOeGJ , OQGSI GdYejd hGdShb , Jage Sdhc GdeTJQjs
Keywords: (3GdCShGb GdMQIs; (3GdJShjbs